Coalition Choice and Elite Personalisation in Partai Amanat Nasional (National Mandate Party) Factionalism 2020 - Anky, Lavica Anky Riswanda (UIN Sunan Ampel Surabaya, 2021)
This paper seeks to analyze the causes of factionalism within PAN in 2020. The findings show that a combination of two factors caused factionalism. First, the policy regarding coalition choice after the 2019 presidential election and elite personalization within the party. We interviewed several DPP PAN (PAN's Central Executive Board) officials and collected documents from the media, previous research, and the party's internal document to obtain the data. PAN's coalition choice was divided into three key factors. First, pragmatism to maximize power (office-seeking) instrumentally by influencing the government's policy. Second, the ideological factor related to party elites' effort to return PAN to a centrist party based on the 2019 election results evaluation where PAN's proximity to Islamic conservatives failed to boost votes. Third, there is regime intervention through legal criminalization threats to several PAN cadres. The personalization of Amien Rais exacerbated this coalition choice in PAN. Amien's influence can bring PAN tendency to be Jokowi's opposition even though it is not a formal party decision. PAN's coalition choice policy led to divisions due to Amien Rais' camp support to the Mulfachri Harahap candidacy in Congress.